Marketing Strategy Analysis of Lemea Ibu Melli's Traditional Food in Lebong Sakti District - Irawati, Gustina; Anggriani, Ida; Febliansa, M Rahman (Universitas Dehasen Bengkulu, 2025)
The purpose of the study was to determine how the marketing strategy analysis of traditional food lemea Ibu Melli in Lebong Sakti District. The sample in this study was 35 people consisting of 5 internal factor respondents and 30 external samples, namely customers of lemea Ibu Melli. Data collection using a questionnaire and the analysis method used was SWOT analysis consisting of the Internal Strategy Factor Matrix (IFAS) and the External Strategy Factor Matrix (EFAS). The results of the study on the marketing strategy of traditional lemea food at the Lemea Ibuk Melli Business can be seen from internal and external factors. Based on the results of the total score obtained, it can be seen that the total value of the strength score owned is 21.75 while the weakness is 11.48 so the internal factor quadrant is 21.75-11.48 = 10.27. The Opportunity Score owned from the strategy is 20.50 and the threat is 10.22. So the external factor quadrant is 20.50 - 10.22 = 10.28. If the two weighted values ​​are combined in the IE matrix, then both will meet in cell I, which supports an aggressive strategy. The marketing strategy that can be carried out by the Lemea Ibuk Melli Business is to carry out the S-O (Strength-Opportunity) strategy or the strength-opportunity strategy is a strategy that uses internal strengths to take advantage of external opportunities. Alternative S-O strategies that can be formulated are maximizing production and promoting on social media.